Implementation process evaluation of an interdisciplinary assistive technology program for infants–toddlers with complex neurodevelopmental disabilities in the Pacific Northwest. - Galvin-McLaughlin, Deirdre; Cochran, Erin; Atkins, Kristi; Crawford, Stephanie; Case, Felicity; Sloane, Bethany (Disability & Rehabilitation: Assistive Technology, 2025)
Although research has demonstrated that tailored intervention for infants and toddlers leads to best outcomes, children who may benefit from interventions incorporating assistive technology (AT) are routinely not enrolled in these services until preschool or later. The purpose of this study is to describe five years of service delivery associated with an interdisciplinary AT program for infants and toddlers with complex neurodevelopmental disabilities. Data describing service delivery was extracted from the medical records of 85 patients who received evaluation or intervention sessions from 2018 to 2023. Data were analyzed using descriptive statistics to examine trends in implementation. Although trends suggest that implementation strategies were successful in providing participants with AT equipment (92% of sample), participation in the program as designed was only completed for 31% and outreach to early interventionists was only completed for 28% of the sample. Analysis of data within constructs and subconstructs of the consolidated framework for implementation research (CFIR1211), revealed that barriers to implementation included: COVID-19 (outer setting), lack of scheduling and administrative staff support (inner setting), cost (innovation) and limited structure to revision (implementation process). Facilitators included: community partnerships with Go Baby Go Oregon (outer setting), insurance reimbursement of virtual care (outer setting), and internal funding for patient equipment (inner setting). Changes in implementation strategies seem warranted to expand the adoption of AT equipment. Proposed strategies include formal strategy review process (structured revisions), altering internal funding source ordering procedures, and adding dynamic outreach options for increased participation by early interventionists. IMPLICATIONS FOR REHABILITATION: The above service delivery and implementation outcomes were extracted from available data on a large sample of infants and toddlers who were enrolled in an interdisciplinary AT clinical program. The data were used to describe trends in clinical procedures, equipment acquisition, and service delivery over the first five years of the program (2018–2023). The findings in this work contribute both to the literature by providing additional descriptions on service delivery, equipment, and clinical needs as well as demonstrating the need for changes in implementation strategy. The findings in this work, including suggested changes for implementation strategy, may help the wider clinical community to adjust practices that could help with the overall implementation of AT.